PENGARUH MOTIVASI DAN LINGKUNGAN KELUARGA TERHADAP KEPUTUSAN MEMILIH PROGRAM STUDI PENDIDIKAN EKONOMI UNIVERSITAS SEBELAS MARET TAHUN ANGKATAN 2014-2017 - -, Angga Verdicha -; -, Harini -; -, Jonet Ariyanto Nugroho - (Jurnal Pendidikan Bisnis dan Ekonomi, 2018)
Angga Verdicha Septiyandi. Motivation and Family Environment influence on Choosing Study Program Office Economic Teachers Training and Educarion Faculty, Universitas Sebelas Maret 2014-2017. Thesis, Teachers Training and Education Faculty, Universitas Sebelas Maret , Juni2018.There are three goals in this research to find the relation between motivation and decision making, to find the relation between family environment and decision making, to find the relation between motivation with family environment and decision making.This research is a qualitative descriptive research. It wasconductedon Nobember 2017-Juni 2018.There search population was the entire students of Office Economic Education batch 2014-2017. The researcher used Proportionate Stratified Random Sampling and the amount of the sample in this research was164students. For the data gathering technique,the researcher used observation and questionnaire.The researcher analyzed the data using multiple linear regression withprerequisitetest. There are two results in this research there is a significant positive relation between family environment and decision making based on thitung>ttabel which is 5.870 > 1.654   at  significance of 5%, there is a significant positive relation between motivation with family environment and decision making based on Fhitung>Ftabelwhich is 98,522>3,89 at significance of 5%, there is a significant positive relation between motivation and decision making based on thitung>ttabelwhichis12.283 > 1.654 at significance of 5%. The amount of donation motivation family environment towards decision making score is 55%. while the rest equal to 45% influenced by other factors not explained in research.